2020
DOI: 10.1128/jcm.01872-19
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the mariPOC Test for Detection of Clostridioides difficile Glutamate Dehydrogenase and Toxins A/B

Abstract: The objective of this study was to evaluate a novel automated random-access test, mariPOC CDI (ArcDia Ltd., Finland), for the detection of Clostridioides difficile glutamate dehydrogenase (GDH) and toxins A and B directly from fecal specimens. The mariPOC test was compared with both the GenomEra C. difficile PCR assay (Abacus Diagnostica Oy, Finland) and the TechLab C. diff Quik Chek Complete (Alere Inc.; now Abbot) membrane enzyme immunoassay (MEIA). Culture and the Xpert C. difficile assay (Cepheid Inc., USA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
1
1
Order By: Relevance
“…In this real-world study, we found that tions. On the other hand, the sensitivity of toxin detection was significantly lower than that described in the kit instructions or other reports (12,17). Furthermore, we found that the clinical characteristics and outcomes of this cohort were similar regardless of toxin status, emphasizing the clinical evaluation of patient status (18).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In this real-world study, we found that tions. On the other hand, the sensitivity of toxin detection was significantly lower than that described in the kit instructions or other reports (12,17). Furthermore, we found that the clinical characteristics and outcomes of this cohort were similar regardless of toxin status, emphasizing the clinical evaluation of patient status (18).…”
Section: Discussioncontrasting
confidence: 48%
“…The awareness of CDI is increasing among Chinese clinicians. However, a methodological evaluation has not yet been established in China to help clinicians diagnose CDI accurately (11,12). Therefore, we aimed to evaluate the performance of VIDAS and QCC tests relative to TC for the diagnosis of CDI and further assess the relationships between clinical factors and different toxin statuses of patients in this real-world study.…”
Section: Objectivesmentioning
confidence: 99%